Pengaruh Penambahan Bubuk Bawang Merah Sebagai Antioksidan Alami Terhadap Kualitas Minyak Goreng Curah - Fardani, Roushandy Asri; Christina, Putu Ayu Winda; Atfal, Bustanul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
The use of bulk cooking oil repeatedly with long storage time results in oil damage, such as increasing the peroxide value and acid number. So far, to overcome this problem, synthetic antioxidants are still used such as Butylated hydroxytoluene (BHT). When BHT added bulk cooking oil will be carcinogenic. Seeing this, it is necessary to look for alternative natural antioxidants. This study aims to seek out the effect of adding natural antioxidants, namely shallot powder to the peroxide value and acid number in bulk cooking oil with storage times of 0, 4, and 8 days. The peroxide number was determined by iodometric titration, while the acid number by acid-base titration. The data obtained were processed with statistics. The results of the statistical data of the Kruskal-Wallis test obtained a sig value of 0.000 less than 0.05, which means that there is an effect of adding shallot powder to the peroxide value and acid number. It shows that shallots are effective as natural antioxidants and can improve the quality of bulk cooking oil.